Innovating the public sector leadership entrepreneurial leadership and employee outcomes in public sector organizations - Ugaddan, Reginald G. (2019)
The increasing popularity of public entrepreneurship and the incessant call for innovative and creative public organizations necessitate an entrepreneurial leadership (EL) approach that is distinct from traditional leadership models. While there have been significant advancements in public management theories of leadership, scant scholarly attention has
been drawn to EL and its impact on public sector organizations. This article fills the gap by using the theoretical frameworks of path-goal, social learning, and social exchange to examine the influence of EL on public service motivation (PSM), affective commitment (AC), and organizational performance (OP). Specifically, this article investigates the mediating
role of PSM through which EL influences AC and OP. The study uses data from the 2015 Public Sector Entrepreneurship Survey collected from Korean public sector employees working within government, executive, and public institution agencies. Results reveal that EL strongly affects outcome variables, particularly those related to OP. In addition, the
impact and extent of EL is higher in public institutions than in executive and government agencies.
Keywords: Entrepreneurship -- Leadership qualities; New Public Management (NPM); Organizational performance -- Measurement; Public Service Motivation (PSM); Leadership -- Theory and practice; Public administration